2011
DOI: 10.1074/jbc.m110.201236
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Receptor (TCR)-induced Tyrosine Phosphorylation Dynamics Identifies THEMIS as a New TCR Signalosome Component

Abstract: Stimulation of the T cell antigen receptor (TCR) induces formation of a phosphorylation-dependent signaling network via multiprotein complexes, whose compositions and dynamics are incompletely understood. Using stable isotope labeling by amino acids in cell culture (SILAC)-based quantitative proteomics, we investigated the kinetics of signal propagation after TCR-induced protein tyrosine phosphorylation. We confidently assigned 77 proteins (of 758 identified) as a direct or indirect consequence of tyrosine pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 68 publications
6
93
1
2
Order By: Relevance
“…In addition, negative selection and CD4 + T cell lineage commitment, which are dependent on intense or sustained TCR signals, respectively, are both impaired in Themis1 −/− mice (2,5). In agreement with these studies of rodent thymocytes, human Themis1 enhances extracellular signal-regulated kinase (ERK) phosphorylation and nuclear factor of activated T cells (NFAT)-activator protein 1 (AP1) luciferase promoter activity in Jurkat cells stimulated with TCR cross-linking antibodies (8). Further biochemical investigation to identify the molecular function of Themis1 has shown that it interacts with two other positive effectors of TCR signaling, phospholipase C-g1 (PLC-g1) (2) and Vav1, a guanine nucleotide exchange factor (GEF) Rho family guanosine triphosphatases (GTPases) (9), in thymocytes, but the importance of these interactions for TCR signaling and T cell development remains obscure.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, negative selection and CD4 + T cell lineage commitment, which are dependent on intense or sustained TCR signals, respectively, are both impaired in Themis1 −/− mice (2,5). In agreement with these studies of rodent thymocytes, human Themis1 enhances extracellular signal-regulated kinase (ERK) phosphorylation and nuclear factor of activated T cells (NFAT)-activator protein 1 (AP1) luciferase promoter activity in Jurkat cells stimulated with TCR cross-linking antibodies (8). Further biochemical investigation to identify the molecular function of Themis1 has shown that it interacts with two other positive effectors of TCR signaling, phospholipase C-g1 (PLC-g1) (2) and Vav1, a guanine nucleotide exchange factor (GEF) Rho family guanosine triphosphatases (GTPases) (9), in thymocytes, but the importance of these interactions for TCR signaling and T cell development remains obscure.…”
Section: Introductionsupporting
confidence: 65%
“…It also contains a bipartite nuclear localization signal (KR-X12-KRRPR) and a C-terminal proline-rich region (PRR) that matches a class II Src homology 3 (SH3) recognition motif. Themis1 is constitutively associated with the cytosolic adaptor protein Grb2 (growth factor receptor-bound protein 2) (5-7) and is recruited to the transmembrane adaptor protein LAT (linker of activated T cells) after TCR engagement, where it becomes rapidly phosphorylated by the protein tyrosine kinase Lck (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we identified THEMIS as an early target of tyrosine phosphorylation downstream of TCR (7). TCR-induced tyrosine phosphorylation of THEMIS depended on the adapters linker for activation of T cells (LAT) and Src homology (SH) 2 domain-containing leukocyte protein of 76 kDa (SLP76), and THEMIS appeared to associate to LAT upon TCR stimulation.…”
Section: T Hymocyte-expressed Molecule Involved In Selection (Themis)mentioning
confidence: 99%
“…Reactions were stopped by adding reducing SDS NuPAGE sample buffer (Invitrogen) and incubation for 5 min at 95˚C, followed by alkylation with 55 mM iodoactamide (Sigma). Proteins were separated on 4-12% gradient Bis-Tris NuPAGE gels (Invitrogen), gels were washed in distilled water, lightly stained with Colloidal Blue (Invitrogen), and subjected to GeLC-mass spectrometry (MS)/MS as described previously (7).…”
Section: Production Of Recombinant Themismentioning
confidence: 99%
“…5 Although its expression is reduced in differentiated T lymphocytes, 6 it is thought to have a role in TcR activation signaling. 7 In turn, PTPRK performs functions related to the maintenance of cell junctions [8][9][10] and in the modulation of epidermal growth factor receptor (EGFR) activity, resulting in an inhibition of cell proliferation. 11,12 Interestingly, both THEMIS and PTPRK have been implicated in normal CD4 þ T-cell development in rodents, suggesting that they participate in common biological processes.…”
Section: Introductionmentioning
confidence: 99%